Ecological Niche Adaptations Influence Transposable Element Dynamics in Pollinating and Non‐Pollinating Fig Wasps - Jing Liu; Yun‐Heng Miao; Hong‐Xia Hou; Da‐Wei Huang; Jin‐Hua Xiao (Ecology and Evolution)
ABSTRACT This study explores how ecological niches influence the dynamics of transposable elements (TEs) in the genomes of pollinating and non‐pollinating fig wasps (NPFWs), and how these ecological factors shape genome evolution. To examine the protective role of fig fruits for pollinators, we compared TE load and dynamics in six pollinating and five NPFW species from six different Ficus species. Phylogenetic analysis was used to assess correlations between genome size, oviposition sites, and TE length. We also analyzed the effects of natural selection and population dynamics on TE accumulation. Significant differences were observed in the total length, number, and types of TEs between pollinators and NPFWs. Phylogenetic analysis indicates that TEs in NPFWs, driven by genome size and oviposition sites, exhibit an expanding state, while pollinators show “dormant” TE landscapes with limited insertions. Despite relaxed selection pressure aimed at prolonging TE retention, pollinators maintain a limited TE abundance, likely due to the contracted population size. Additionally, numerous cis‐regulatory modules derived from TEs are located near genes involved in environmental information processing, emphasizing their potential role in adaptation. Our findings highlight the role of ecological niches, represented by oviposition sites, in shaping the TE dynamics of fig wasps. These results provide new insights into how ecological pressures influence genome evolution and adaptation in insects.